(untitled) (AMJ (Advanced Medical Journal), 2024)
Background and objectives: Ankylosing spondylitis is a chronic inflammatory disorder that affecting axial and non-axial joints leads to a loss of mobility and function over time. The aim of this study is to evaluate the cardiac involvement using transthoracic echocardiography. Methods: A case-control research study took place at Rizgary Teaching Hospital Rheumatology Department between January 2022 and March 2023. Inclusion criteria involved those patients diagnosed with ankylosing spondylitis based on the Assessment of Spondylarthritis International Society criteria for axial spondylarthritis. Transthoracic echocardiography (vivid machine) had been performed for all the participants and parameters such as right and left ventricle dimension, aortic root dimension, left atrium dimension, interventricular septum thickness in diastole and ejection fraction had been documented. Results: This study revealed that transthoracic echocardiography findings of patients with ankylosing spondylitis with diastolic dysfunction in 12%, mitral regurgitation in 8%, mitral prolapse in 10% and 2% of each of anteroseptal hypokinesia, dilated aortic root and aortic regurgitation. The study demonstrated a significant increase in right ventricular, aortic, and left atrium dimensions in patients with ankylosing spondylitis with a p value of 0.0001, 0.001 and 0.001 respectively. In terms of ejection fraction; this study showed a significant decrease in ejection fraction in cases of ankylosing spondylitis with a mean of 64.3% with a p value of 0.004. Conclusion: Tricuspid regurgitation and a drop in ejection fraction are the two significant findings among patients with ankylosing spondylitis.